Margarita Práxedes Muñoz (1848 - 1909) Peru's first female university graduate and her life in the Southern Cone - Vera de Flachs, María Cristina (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2023)
Objective: This article examines the life and work of Margarita Praxis Muñoz, the first female graduate from the Universidad de San Marco with a bachelor's degree in Science and Letters, to later become a Peruvian physician, scientist, feminist and progressive who made her life pilgrimage through four countries of the Southern Cone. Originality/support: A forgotten character in her country who starts to be appreciated at the end of the 19th century by several literary women who analyzed her novel in particular. The originality of this study lies in the focus of her life in Argentina, where she ended her days. Method: Biographical. The methodology followed in this work consisted of an analysis of her intellectual production in relation to her academic training in order to observe her ideas and application in context. Strategies/ Data Collection: For this biography we have made use of her own work and that of the researchers who have studied her, they are listed in the attached bibliography. Due to the scarcity of available data, interviews were conducted with Argentine historians of the Santiago region where she ended her days as a physician in the quebracho plantations. Conclusions:  The character studied will allow us to delve into the historical and educational context of the women from the places she lived in and will show us her active participation in different fields. In this way, we go through her interests and those of the people she shared her life with. We approach the problems of her time, the history of ideas, and the daily life of the first women who dared to enter the world of men. Forgotten for a long time, the value of Margarita Praxis Muñoz is acknowledged today, in this article.